Gender-preferential Linguistic Elements in Applied Linguistics Research Papers: Partial Evaluation of a Model of Gendered Language - Reza Ghafar Samar; Mohsen Shirazizadeh (Journal of Applied Linguistics, 2010)
This article intended to investigate whether the gender-preferential linguistic elements found by Argomon, Koppel, Fine and Shimoni (2003) show the same gender-linked frequencies in applied linguistics research papers written by non-native speakers of English. In so doing, a sample of 32 articles from different journals was collected and the proportion of the targeted features to the whole number of words was calculated. The results indicated that, although the gender-linked patterns of use for many of those features were also observed in our sample, the difference between men and women in the frequency of using those elements was not statistically significant. This non-significant difference shows that either the confinements of genre or those of using a second language or both are keeping L2 writers from expressing their gender to its fullest capacity in the texts they produce.